WRITING PROBLEMS IN SENIOR HIGH SCHOOL (SMAN) 2 BANDAR - ADINDA PUJA ANTIKA; DINDA M HASIBUAN; EKY SYAHDITRA SITORUS; YESIKA HELTISA SIREGAR; SELVIANA NAPITUPULU (CV KULTURA DIGITAL MEDIA, 2022)
The study is aimed to investigate the internal and external problems in Writing by the Senior High Students in one of the school in Simalungun SMA Negeri 2 Bandar. The sample of this study is the eleventh grade students having low ability in Writing. This research is a qualitative study using purposive sample. In collecting the qualitative data the researchers did observation, and distributed questionnaire. This study reveals some findings related to the students’ low ability in writing.